Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s00068-015-0565-1
|View full text |Cite
|
Sign up to set email alerts
|

Cervical collar effect on pulmonary volumes in patients with trauma

Abstract: Cervical collar applications in trauma patients cause a significant decrease in lung capacity and spirometry parameters. Patients suffering from lung diseases and respiratory distress require special attention which means that the cervical collar should be removed as soon as cervical injuries are ruled out so as to avoid hypoxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…In line with previous publications, additional publications proposing possible harmful effects were found. For example, longer stay in the emergency room [43], decreased lung function [44], development of pressure ulcers [13, 45], impeded airway management [22], worsening of existing cervical injury [22], severe neurological deterioration in patients with ankylosing spondylitis [22], triggering of non-compliance or agitation and even increased spinal movement due to pain or discomfort [22] as well as possible elevation of intracranial pressure [46].…”
Section: Resultsmentioning
confidence: 99%
“…In line with previous publications, additional publications proposing possible harmful effects were found. For example, longer stay in the emergency room [43], decreased lung function [44], development of pressure ulcers [13, 45], impeded airway management [22], worsening of existing cervical injury [22], severe neurological deterioration in patients with ankylosing spondylitis [22], triggering of non-compliance or agitation and even increased spinal movement due to pain or discomfort [22] as well as possible elevation of intracranial pressure [46].…”
Section: Resultsmentioning
confidence: 99%
“…These results are supported by other studies analyzing the effects of cervical collars. 37,38 Because many complications seem to accompany the use of a cervical collar, 4,[36][37][38] it remains questionable if the general application of a cervical collar in almost every trauma patient represents best practice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, one study found that application of a cervical collar causes a significant decrease in lung capacity and spirometry parameters, [3] but they did not examine the consequences hereof, such as whether this caused a subjective experience of dyspnoea.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have, however, raised concerns about immobilisation and questioned its efficacy, the risk of over-triage and potential harmful effects as the evidence of the benefits of spinal immobilisation has been limited [1, 2]. Furthermore, several studies have identified complications related to immobilisation, such as tissue ischemia, pressure ulcers and decreased lung volumes [35]. These complications have, however, been measured objectively without accounting for the subjective experience secondary thereto, such as possible pressure, discomfort and dyspnoea related to being immobilised.…”
Section: Introductionmentioning
confidence: 99%